Rigid and soft modularity: the case of a Beiruti shoreline - El-Khoury, Roula (2024)
This paper explores spatial systems of modularity on the shoreline of Ein el Mrayseh located in Beirut. The modular systems are studied from a contextual lens while observing different modular interventions as design strategies on this shoreline. The Ein el Mrayseh corniche is one of the few remaining public spaces of Beirut, and is considered one of the most important outlet for the city residents. It is used by different types of groups, from different classes and backgrounds. Based on a series of observations, the paper analyses modular interventions by different stakeholders on this stretch. Two terms were coined: rigid and soft modularity, as linguistic and analytical modes to understand the spatial practices of Ein el Mrayseh. The paper argues that the users of this public space have developed soft modular strategies - dynamic and in constant flux, as a mean to tame the rigid modular strategies enforced on the site and to appropriate the space.